Dimensional Matching of Polycyclic Aromatics with Rectangular Metallacycles: Insertion Modes Determined by [CH⋅⋅⋅π] Interactions. Issue 45 (19th September 2013) - Alvariño, Cristina; Pía, Elena; García, Marcos D.; Blanco, Víctor; Fernández, Alberto; Peinador, Carlos; Quintela, José M.
Abstract A family of PdII/PtII dinuclear receptors, designed to give a smooth increase in their cavity lengths (from 7.46–13.78 Å), is presented. Their inclusion complexes with a representative set of polycyclic aromatic substrates (naphthalene, carbazol, pyrene, and benzo[a]pyrene), were characterized and studied in aqueous solution and the solid state. By taking into account the dimensions of both receptors and substrates, an excellent complementarity was found between the size of the receptors and their ability to complex a given substrate. Furthermore, this dimensional matching results in specific binding modes depending on the ability of the guest to establish stabilizing [CH⋅⋅⋅π] interactions with the host.